Electrochemical non-invasive biosensors for humans and plants health monitoring (2023)
Non-invasive biosensors offer significant advantages over traditional invasive methods, as they eliminate discomfort, reduce risks of infection, and enable continuous monitoring without disruption. In humans, these sensors enable the possibility of early disease diagnostic even before symptoms manifest, leading to improved disease management and more effective treatment strategies. In the agriculture field, non-invasive biosensors offer a non-destructive and efficient approach to assess plant responses to environmental stresses. By understanding how plants adapt and respond to different biotic and abiotic stresses, researchers can develop strategies for crop improvement, optimize resource utilization, and enhance agricultural productivity in a sustainable manner. However, there are several challenges that need to be addressed, which include improving the sensitivity, selectivity, and stability of the biosensors, as well as enhancing their compatibility with diverse plant species and environmental conditions. Additionally, novel strategies are needed to expand the range of analytes that can be detected non-invasively, allowing for a comprehensive understanding of plant physiological processes. Research on novel non-invasive biosensors holds immense potential for advancing healthcare practices, promoting preventive medicine, and enhancing our understanding of plant stress physiology, thereby contributing to human well-being and global food security. This dissertation presents the development and application of three novel biosensor platforms for non-invasive health monitoring in both humans and plants. The first platform is based on a stand-alone point-of-care (POC) device for rapid (< 10 min) SARS-CoV-2 diagnosis infection in human swab or saliva using an antigen modified screen-printed carbon electrode (SPCE) and electrochemical impedance spectroscopy (EIS) technique as quantification method. The sensor exhibits an impressive limit of detection (LOD) of 1 fg/mL and a remarkable selectivity (> 90%). These achievements represent substantial enhancements, with the LOD surpassing traditional RT-PCR methods by over 23% and an astounding 99.98% improvement compared to a relevant vertical-flow cellulose-based technology currently available. Additionally, this innovative technology reduces the diagnostic time to just 10 minutes, marking a remarkable 91.67% improvement compared to the time-consuming RT-PCR method and an important 33.33% reduction compared to similar approaches. In the second platform, a chronopotentiometry wearable biosensor, based on an iontophoretic system for plant exudation and a glucose oxidase (GOx) modified SPCE, is proposed for glucose determination in plants under light and temperature stress. This sensor achieves a low LOD of 9.4 μmol L-1 and demonstrates a sensitivity of 22.7 nA/μmol L-1⋅cm-2, exposing significant improvements of over 130.98% and 99.95%, respectively, compared to a relevant microneedle-based biosensor designed for in-vivo glucose monitoring in plants previously published in the state of the art. In the last platform, a bioagent-free chronopotentiometry wearable biosensor based on the iontophoretic system and a laser-induced graphene (LIG) electrode is proposed for non-invasive salicylic acid monitoring in plants under drought and salinity stress. With a sensitivity of 82.3 nA/μmol L-1⋅cm-2 and an LOD of 8.2 μmol L-1, the proposed sensor demonstrates remarkable improvements of over 99% in sensitivity and 90% in linearity, compared to the first non-invasive SA biosensor presented in the state of the art. Overall, the presented platforms represent significant advancements in the field. These biosensors hold great potential for revolutionizing healthcare and agriculture, enabling efficient and timely monitoring of health conditions, stress responses, and disease detection.